(untitled) (Journal of actual problems of jurisprudence, 2019)
In the article the role of barrister in ensurance of contest and equality of parties, the necessity of adoption of the RK Law “ About quilified legal help”, in which barrister’s duties and rights, mechanism and order of carrying out activity on producing procedural actions, consequences of not fulfilling barrister’s legal demands should be foreseen, complex of measures, directing to incresing barrister’s status in criminal procedure are suggested.